Evaluating Human-Computer Co-creative Processes in Music: A Case Study on the CHAMELEON Melodic Harmonizer - Zacharakis, Asterios; Kaliakatsos-Papakostas, Maximos; Kalaitzidou, Stamatia; Cambouropoulos, Emilios (Frontiers in Psychology, 2021)
CHAMELEON is a computational melodic harmonisation assistant. It can harmonise a given melody according to a number of independent harmonic idioms or blends between idioms based on principles of conceptual blending theory. Thus, the system is capable of offering a wealth of possible solutions and viewpoints for melodic harmonisation. This study investigates how human creativity may be influenced by the use of CHAMELEON in a melodic harmonisation task. Professional and novice music composers participated in an experiment where they were asked to harmonise two similar melodies under two different conditions: one with and one without computational support. A control group harmonised both melodies without computational assistance. The influence of the system was examined both behaviourally, by comparing metrics of user-experience, and in terms of the properties of the artifacts (i.e., pitch class distribution and number of chord types characterising each harmonisation) that were created between the two experimental conditions. Results suggest that appreciation of the system was expertise-dependent (i.e., novices appreciated the computational support more than professionals). At the same time, users seemed to adopt more explorative strategies as a result of interaction with CHAMELEON based on the fact that the harmonisations created this way were more complex, diverse and unexpected in comparison to the ones of the control group.